2023
DOI: 10.1017/cts.2023.624
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an online research best practices training for community health workers and promotoras

Susan L. Murphy,
Gina M. Jay,
Elias M. Samuels
et al.

Abstract: Introduction: Community health workers and promotoras (CHW/Ps) have a fundamental role in facilitating research with communities. However, no national standard training exists as part of the CHW/P job role. We developed and evaluated a culturally- and linguistically tailored online research best practices course for CHW/Ps to meet this gap. Methods: After the research best practices course was developed, we advertised the opportunity to CHW/Ps nationwide to complete the training online i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…Over the course of developing and launching this training, we found that there is a pervasive need for CHWs in New York City and the U.S. broadly to expand their knowledge of clinical research. Murphy et al identified a similar gap and developed an online course for CHWs on research best practices ( Murphy et al, 2023 ). The training was received positively as both useful and relevant by both English-speaking and Spanish-speaking CHWs, further demonstrating a need for this training.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the course of developing and launching this training, we found that there is a pervasive need for CHWs in New York City and the U.S. broadly to expand their knowledge of clinical research. Murphy et al identified a similar gap and developed an online course for CHWs on research best practices ( Murphy et al, 2023 ). The training was received positively as both useful and relevant by both English-speaking and Spanish-speaking CHWs, further demonstrating a need for this training.…”
Section: Discussionmentioning
confidence: 99%
“…A well-trained community-based workforce in research is better prepared to engage the community actively while enhancing their knowledge of research and participation in trials. In addition, as we recruit more diverse participants into clinical research, it will be imperative to have a community-centered, multi-lingual, and diverse, research-trained workforce that reflects the population ( Murphy et al, 2023 ). For example, CHWs who understand their clients’ health conditions are able to navigate them to eligible therapeutic clinical trials.…”
Section: Introductionmentioning
confidence: 99%